Influence of slaughter season, muscle type and gluconeogenesis precursors on intramuscular fat quality of ruminant meats - Assunção, José Miguel Pestana (2012)
Tese de Doutoramento em Ciências Veterinárias, especialidade de Segurança Alimentar